2010
DOI: 10.1088/0960-1317/20/4/045007
|View full text |Cite
|
Sign up to set email alerts
|

Replication performance of Si-N-DLC-coated Si micro-molds in micro-hot-embossing

Abstract: Micro-hot-embossing is an emerging technology with great potential to form micro-and nano-scale patterns into polymers with high throughput and low cost. Despite its rapid progress, there are still challenges when this technology is employed, as demolding stress is usually very high due to large friction and adhesive forces induced during the process. Surface forces are dominating parameters in micro-and nano-fabrication technologies because of a high surface-to-volume ratio of products. This work attempted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…This silicon oxide layer prevents direct contact between the film and ball when sliding, resulting in the low friction forces. Additionally, in the case of the Si-N-DLC film, the result indicates a low friction coefficient due to the incorporation of silicon and nitrogen [21]. However, the nitrogen content may be less influential than the silicon content, which was described in the literature [22].…”
Section: Resultsmentioning
confidence: 73%
“…This silicon oxide layer prevents direct contact between the film and ball when sliding, resulting in the low friction forces. Additionally, in the case of the Si-N-DLC film, the result indicates a low friction coefficient due to the incorporation of silicon and nitrogen [21]. However, the nitrogen content may be less influential than the silicon content, which was described in the literature [22].…”
Section: Resultsmentioning
confidence: 73%
“…In general, the DLC film spectrum can be fitted into Gaussian peaks at approximately 1550 cm −1 (G peak) and 1355 cm −1 (D peak). 4 The fitting parameters: peak position and relative integrated intensity ratio (ID/IG), are used for characterized the materials. [5][6][7] The Raman spectrums of N-DLC film presents a G peak near 1525 cm −1 to 1565 cm −1 and D peak was measured near 1355 cm −1 to 1360 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Other studies also showed that mould and polymer materials have an effect on the adhesion phenomena (Guo et al 2007a, Saha et al 2010, Jaszewski et al 1999, Park et al 2004. For instance, the application of coatings on the mould surface can improve the demoulding in HE as it reduces the influence of the chemical and physical interactions.…”
Section: Factors Affecting Demouldingmentioning
confidence: 99%